2020
DOI: 10.7554/elife.53515
|View full text |Cite
|
Sign up to set email alerts
|

ParB spreading on DNA requires cytidine triphosphate in vitro

Abstract: In all living organisms, it is essential to transmit genetic information faithfully to the next generation. The SMC-ParAB-parS system is widely employed for chromosome segregation in bacteria. A DNA-binding protein ParB nucleates on parS sites and must associate with neighboring DNA, a process known as spreading, to enable efficient chromosome segregation. Despite its importance, how the initial few ParB molecules nucleating at parS sites recruit hundreds of further ParB to spread is not fully understood. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(159 citation statements)
references
References 56 publications
10
132
0
Order By: Relevance
“…Recent evidence has added a new nucleotide cofactor to partition with the demonstration that ParB binds and hydrolyses CTP (43)(44)(45). Further, the evidence indicates that CTP, which binds to the N-terminal domain of ParB, allows ParB to clamp onto DNA when it loads at parS, and facilitates loading multiple ParB molecules.…”
Section: Kinetics Of Nsdna Binding Is Fundamental To Partition Activitymentioning
confidence: 99%
“…Recent evidence has added a new nucleotide cofactor to partition with the demonstration that ParB binds and hydrolyses CTP (43)(44)(45). Further, the evidence indicates that CTP, which binds to the N-terminal domain of ParB, allows ParB to clamp onto DNA when it loads at parS, and facilitates loading multiple ParB molecules.…”
Section: Kinetics Of Nsdna Binding Is Fundamental To Partition Activitymentioning
confidence: 99%
“…Such a study is also be complicated with the transient interactions between ParA and ParB that both exist in different biochemical states Ah-Seng et al 2009). The recent findings that ParB binds CTP (Soh et al 2019;Osorio-Valeriano et al 2019;Jalal, Tran, and Le 2020) and that parS-mediated CTP hydrolysis stimulates ParA interaction (Osorio-Valeriano et al 2019; Jalal, Tran, and Le 2020) could open interesting molecular clues to control this interaction. Moreover, our model describes the PC partitioning along the nucleoid surface as a 2D problem.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence recovery after photo-bleaching (FRAP) experiments have shown that ParB F molecules rapidly exchange between different clusters, further highlighting the dynamic nature of cages of ParB-DNA in vivo [70]. The nucleation and caging model has also been shown applicable to the Vibrio cholerae chromosomal ParB-parS system, suggesting that this dynamic self-assembly mechanism might be conserved from plasmids to chromosomes [ between the nucleation and translocation modes [52,71]. Mutant proteins (N112S and N172A of B. subtilis and M.…”
Section: Model 3-caging Parb and Dnamentioning
confidence: 99%
“…Recent studies have uncovered a new cofactor of ParB [ 51 , 52 ]. Various plasmid- and chromosome-encoded ParB and ParB-like proteins have been found to bind and hydrolyse cytidine triphosphate (CTP) to cytidine di-phosphate (CDP) and inorganic phosphate [ 51 , 52 , 71 ]. A co-crystal structure showed CDP binding to the arginine-rich patch at the NTD of B. subtilis ParB (CTP was hydrolysed to CDP during crystallization) [ 52 ].…”
Section: Parb– Pars Interaction and The Assembly Omentioning
confidence: 99%
See 1 more Smart Citation